Biological maturation, relative age and self-regulation in male professional academy soccer players: A test of the underdog hypothesis. (November 2018) - Cumming, Sean P.; Searle, Chris; Hemsley, Janie K.; Haswell, Finlay; Edwards, Hannah; Scott, Sam; Gross, Aleks; Ryan, Desmond; Lewis, Jeff; White, Paul; Cain, Andrew; Mitchell, Siobhan B.; et al.
Abstract: Objectives: The main and interactive effects of biological maturity status and relative age upon self-regulation in male academy soccer players are considered. Consistent with the 'underdog' hypothesis, whereby relatively younger players may benefit from competitive play with older peers, it was predicted later maturing and/or relatively younger players would report more adaptive self-regulation. Design: Cross-sectional study. Method: Players (n = 171, aged 11–16 years) from four English professional soccer academies completed the modified Soccer Self-Regulation Scale. Date of birth, height, weight and parental height were obtained. Relative age was based on birth quarter for the selection year. Maturity status was based upon percentage of predicted adult height attained. Results: Linear regression models showed later maturation was inversely associated with adaptive self-regulation, while relative age was unrelated to self-regulation. Conclusions: In partial support of the underdog hypothesis, later maturing players appear to possess a psychological advantage. Highlights: Results of the present study partially support the 'Underdog Hypothesis'. Although an apparent selection bias towards relatively older players was found, the results indicated no association between relative age and self-regulation. Consistent with the 'underdog' hypothesis, later maturing players are more likely to possess and/or develop more adaptive self-regulation skills, in particular self-evaluation and reflection. Exposing early maturing players to more challenging learning environments in soccer may facilitate the development of more adaptive psychological skill sets. Soccer academies should focus on retaining late maturing players within the academy systems and challenging players who are advanced in maturation.